THE DISCOVERY OF SUBJECTIVITY AS A METAPHYSICAL PREREQUISITE FOR ANTHROPOLOGIES OF ALL KINDS - Kulueva Flyura Gaynitdinovna (American Journal of Bioscience and Clinical Integrity, 2025)
The work examines the philosophy of modern times, which emphasized the discovery of the natural foundations of man. It is shown that in the naturalistic The concept considers man as an element of nature, subject to its laws. The main naturalistic models, the development of biologizing and sociologizing are considered. strategies for understanding human nature